2003
DOI: 10.1093/nar/gkg415
|View full text |Cite
|
Sign up to set email alerts
|

Canonical nucleosides can be utilized by T4 DNA ligase as universal template bases at ligation junctions

Abstract: T4 DNA ligase catalyzes the template-dependent ligation of DNA. Using T4 DNA ligase under specific experimental conditions, we demonstrate that each of the four canonical nucleosides, centrally located on a template molecule such that they flank the site of ligation, can direct the ligation of nucleic acids regardless of the identity of the terminal nucleosides being covalently joined. This universal templating capability extends to those positions adjacent to the ligation junction. This is the first report, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 42 publications
1
32
1
Order By: Relevance
“…6D ) are more readily tolerated [31], [34]. In a previous study, nearly all possible combinations of downstream single-nucleotide mismatches yielded >80% ligated product under conditions of low ATP concentrations even with multiple consecutive mismatches [22], [31]. This tolerance for mismatches on the downstream side is sharply contrasted by the results obtained in the present study, where a single tethered nucleotide provides the interaction energy on the downstream side.…”
Section: Discussioncontrasting
confidence: 96%
“…6D ) are more readily tolerated [31], [34]. In a previous study, nearly all possible combinations of downstream single-nucleotide mismatches yielded >80% ligated product under conditions of low ATP concentrations even with multiple consecutive mismatches [22], [31]. This tolerance for mismatches on the downstream side is sharply contrasted by the results obtained in the present study, where a single tethered nucleotide provides the interaction energy on the downstream side.…”
Section: Discussioncontrasting
confidence: 96%
“…For dbr1Δ whole-cell RNA treated with RNase R and Prp16-IP RNA treated with RNase R, LIT-seq libraries were analyzed similarly, but with several modifications. First, after removal of the adapters, we also removed the two most 3 ′ nucleotides in the 5 ′ library and the two most 5 ′ nucleotides in the 3 ′ library, because the downstream analysis revealed that these nucleotides, which corresponded to the MmeI-derived overhang sequences were frequently mutated, likely due to the tolerance of mismatches in the ligation of a duplex by T4 DNA ligase (Alexander et al 2003); for reasons that are not clear, such mutagenesis was not a significant problem for the RNase R-untreated libraries. After removal of these two nucleotides, reads with 14-15 nt for the 5 ′ libraries and 18-19 nt for the 3 ′ libraries were retained as tags.…”
Section: Bioinformaticsmentioning
confidence: 99%
“…[11] Although the in vivo repair system requires high fidelity for DNA ligation, surprisingly, T4 DNA ligase has been reported to ligate a wide range of substrates such as those containing a gap or one or more mismatches, and even two single-stranded DNAs in the total absence of a template. [12] Moreover, it can variously ligate two DNAs, two RNAs, or even DNA and RNA heteronucleic acids either on a DNA or on an RNA template.…”
Section: Resultsmentioning
confidence: 99%